Konflik dan Negosiasi dalam Organisasi - Ansori Ansori; Asi Angelia Safitri; Nur Adilla; Sigit Hardi Ramadhani (Universitas 17 Agustus 1945 Semarang, 2024)
When two persons or organizational groups hold divergent views, conflict frequently results. Conflict arises in organizations almost always. There are a number of theories on conflict that help us comprehend it when it happens. The process of reaching a discussion-based agreement between two parties is called negotiation. One may say that negotiations within the organization are the outcome of a previously negotiated agreement between members. Because each member of an organization has a different opinion, there will inevitably be disputes in the group. Here is where the organization's function will be utilized, as each member will weigh, haggle, and discuss what agreement will be made from the many viewpoints of the members of the organization.